EDITORIAL - Balmant, Wellington (Revista de Engenharia Térmica, 2021)
The editorial of Thermal Engineering of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. Mathematical modeling is a powerful tool used in engineering when one wants to design and optimize and equipment and/or processes. The main idea behind a mathematical model is to be able to simulate, as accurately as possible, the behavior of any physical system, real or virtual. However, the task of creating a mathematical model is far from simple. For the sake of comparison, disciplines of physics also propose mathematical models, but these models need to be universal. In engineering, this degree of universality is practically impossible. In reality, a good mathematical model for engineering is the one that is a good tool, assisting the design and optimization of equipment and systems. But which model should we choose when we find ourselves in real life engineering problems? Unfortunately, mathematical models for engineering are quite subjective. It takes into account what each author of the model saw and what problem he/she wanted to solve. That is why for the same system, for example, a shell and tube heat exchangers, there are multitude mathematical models proposed with different features, from highly complex models that use computational fluid dynamics to the simplest models used in undergraduate courses. This makes creativity and analytical skills very important when designing and optimizing a real system in view of the fact that design failures can generate monetary and human life losses. Choosing the right mathematical model is not a simple task, especially in unconsolidated areas, which are generally those where there is a great interest in applied research. Due to the very large number of existing mathematical models, engineers generally choose to propose their own mathematical model. A classification system for mathematical models would be very useful to find what mathematical models are most useful for a given situation. The mission of Thermal Engineering is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.